1986
DOI: 10.3109/03009748609092663
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin versus Penicillamine in Rheumatoid Arthritis: One-year Results from a Prospective Clinical Investigation

Abstract: Forty patients with definite or classical active rheumatoid arthritis were stratified by the minimization procedure to auranofin (6 mg/day) or penicillamine (go slow and low regime). This investigation is a prospective planned 3 year patient and 'doctor-open' as well as 'doctor-blind' clinical trial. This article describes the results after 12 months. Both drugs decreased disease activity and improved the functional capacity in a similar way. Two patients in the auranofin group and 5 in the penicillamine group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…In another study, injectable gold and AUR were found to be equally effective, with injectable gold causing more serious toxicity (19). In double-blind comparative trials, the efficacy and safety of AUR and DP were comparable (20,21).…”
mentioning
confidence: 96%
“…In another study, injectable gold and AUR were found to be equally effective, with injectable gold causing more serious toxicity (19). In double-blind comparative trials, the efficacy and safety of AUR and DP were comparable (20,21).…”
mentioning
confidence: 96%
“…For our primary analysis of all 132 studies (represented by 130 publications) we used the most frequently reported outcome, TJC. This included imputed TJC values for studies that did not measure TJC (eMethods 5 in Supplement 1), denominated TJCi.…”
Section: Methodsmentioning
confidence: 99%
“…Frequently used medications associated with drug‐induced taste disturbances, identified primarily from case reports 5–51 , are listed in Table 1. Additional lists of medications implicated in taste disorders can be found elsewhere 3…”
Section: Effects Of Medication On Tastementioning
confidence: 99%
“…Xerostomia management involves moistening mucus membranes and increasing salivary secretion. Sucking on hard candy, selecting an agent with lower anticholingergic properties, discontinuing the offending medication, using artificial saliva, and/or using cholinergic agents (eg, pilocarpine 5 mg orally, 3 times daily) may increase the amount of fluid in the mouth 2,9–93 …”
Section: Management Of Taste Disturbancesmentioning
confidence: 99%